The Important Role of Environmental Stewardship Groups in Supporting Human Health and Well-Being - Dacks, Rachel; McMillen, Heather; Heimuli, Pua; Kahaleua, Kimberly; Burgess, Sanoe; Giardina, Christian P.; Francisco, Kainana; Ticktin, Tamara (Frontiers in Sustainable Cities, 2021)
The human health and wellbeing benefits of nature are well known. The COVID-19 pandemic has disrupted the work of environmental stewardship groups, especially those that facilitate access to and/or provide opportunities to engage with nature. To understand the impacts of this disruption on stewardship groups and their volunteers in Hawaiʻi, we: (i) conducted semi-structured interviews with 20 leaders of stewardship groups on Oʿahu; and (ii) surveyed 85 individuals who volunteer with stewardship groups across the state. We found that some groups were negatively impacted by COVID-19-related funding losses, volunteer activity cancellations, and thus a reduced workforce. We also found that some groups were able to secure new pandemic-specific funding sources and increase their online presence. Many groups were able to strengthen their connections to community through efforts to respond to COVID-19 driven needs of the community, for example meeting nutritional needs of families through food or crop plant distributions. When asked what they missed the most about volunteering with stewardship groups, over half of surveyed respondents identified the social benefits of volunteering, including feeling a sense of community. Over a third of respondents said they missed engaging with the land/place. Nearly a third indicated that a lack of engagement with these groups during the pandemic has negatively affected them psychologically. Our results highlight the significant yet underappreciated role that stewardship groups play in community and individual wellbeing, and how a large-scale crisis can lead to innovative adaptations with important implications for social resilience.